ETNOBOTANI JOKO KAHA : TRADISI PENYAMBUTAN TAMU PADA MASYARAKAT DESA BOBANEHENA DI HALMAHERA BARAT, MALUKU UTARA - Anisatu Z. Wakhidah; Marina Silalahi; Dimas H. Pradana (Jurnal Pro-Life, 2018)
Joko kaha is a tradition of welcoming guests (domiciled persons) that are still implemented by West Halmahera Community, especially at Bobanehena Village. The tradition uses a variety of plants in its implementation. Based on the data, the research about ethnobotanical study of joko kaha tradition is still lack even none. This is a preliminary joko kaha study to document the used plants in joko kaha tradition. This study also examines the benefits of tradition associated with the scientific literature and conservation attitudes that performed by Bobanehena Village communities. Ethnobotanical data were taken using semi-structured interview method which was taken from key respondents. Plant data taken in the field with key repondents, made herbarium then identified. The results show that there are 5 plants species used in the tradition of joko kaha, they are Graptophyllum pictum (L.) Griff., Graptophyllum pictum 'Roseum variegatum', Eleusine indica (L.) Gaertn., Oryza sativa L., and Curcuma longa L. After learned, the essence of the joko kaha tradition actually is to provide salvation for the person who will start a new period in his/her life. While the attitude of community conservation of the plant used was considered good that have been proven by the community was able to cultivate the used plants at their home garden.Keywords : Tradisi joko kaha, penyambutan tamu, etnobotani, desa bobanehena